Beyond Stereotypes: Personal Perceptions Study of Tionghoa Ethnicity on Relations with Indonesian Society - Nufus, Achmad Busrotun; Malihah, Elly; Darmawan, Cecep; Anggraeni, Leni; Budimansyah, Dasim (KnE Social Sciences, 2024)
Indonesia is a country with diverse tribes, religions, ethnicities, and traditions. Although Indonesia makes a unique contribution to the life of the archipelago and its citizens, it does not rule out the risk of disputes and conflict. One of them is the existence of ethnic differences, which give rise to stereotypes of certain ethnicities, such as Tionghoa. Not all stereotypes are justified and real. Indonesian history records the existence of social conflicts born from inter-ethnic stereotypes, such as during the 1998 riots. Therefore, this research aims to explore individual lived experiences and subjective viewpoints and provide a platform for authentic voices that are often unheard in discussions of ethnicity and identity. So, this article provides insight into how ethnic Tionghoa people strengthen their perceptions of existing stereotypes. This research uses a qualitative approach with a case study method. The research data was obtained through interviews with 30 ethnic Tionghoa people accompanied by participant observation. In contrast, data analysis took a thematic approach to identify patterns and themes that emerged from the results of interviews and observations. The research findings show that an understanding of the diversity of individuals and society that has not been fully accepted reflects challenges, including political history that influences negative perceptions. Unfortunately, the complexity of social relations means that some informants feel that the Tionghoa ethnic community tends to be closed, creating the impression of a lack of unity in Indonesian society. This research is important to explore how the reality of the lives of ethnic Tionghoa people does not fully conform to the prevailing stereotype. Keywords: stereotypes, Tionghoa, public relations